MOTIVASI MAHASISWA MENJADI ENTREPRENEUR (Studi Pada Mahasiswa Administrasi Bisnis Angkatan 2018 Universitas Malikussaleh) (Negotium: Jurnal Ilmu Administrasi Bisnis, 2023)
ABSTRACTMotivation is the provision of a driving force or impetus that creates one’s work enthusiasm so that they want to work together, work effectively and with integrity with all efforts to achieve satisfaction. Entrepreneururship is the process of creating something different by devoting all of his time and energy accompanied by taking financial, psychological, social risks and receiving rewards in the form of money and personal satisfaction. Entrepreneurial student motivation is influenced by various motivational factors, both internal and ekternal factor. The research object is on the campus of Malikussaleh University, faculty of social and political sciences. The cause of the low interest of students in entrepreneurship. The method used in this study is a qualitative method with a descriptive approach. To obtain complete data and information in this study, data collection techniques in the form of observation, interviews and documentation werw used. The data reduction, data presentation and conclution drawing. The result show that the motivation of Business Administration students for entrepreneurship is students who have talent for entrepreneurship, are confident, creative, innovate, have a passion for entrepreneurship. And to be independent and have their own income. The motivational factors for entrepreneurial students are due to internal and external factors and the low interest of students in entrepreneurship due to lack of capital..